Serum Matrix Metalloproteinase 9 and Macrophage Migration Inhibitory Factor (MIF) Are Increased in Young Healthy Nonobese Subjects with Positive Family History of Type 2 Diabetes - Agnieszka Nikołajuk; Natalia Matulewicz; Magdalena Stefanowicz; Monika Karczewska-Kupczewska (International Journal of Endocrinology)
Insulin resistance increases the risk for cardiovascular disease (CVD) even in the absence of classic risk factors, such as hyperglycemia, hypertension, dyslipidemia, and obesity. Low-grade chronic inflammatory state is associated both with insulin resistance and atherosclerosis. An increased circulating level of proinflammatory proatherogenic factors and biomarkers of endothelial activation was observed in diabetes and CVD. The aim of our study was to assess serum proatherogenic and proinflammatory factors in young healthy nonobese subjects with positive family history of type 2 diabetes. We studied 74 young healthy nonobese subjects with normal glucose tolerance (age < 35 years, BMI < 30 kg/m2), 29 with positive family history of type 2 diabetes (relatives, 25 males and 4 females) and 45 subjects without family history of diabetes (control group, 39 males and 6 females). Hyperinsulinemic-euglycemic clamp was performed, and serum concentrations of monocyte chemoattractant protein-1 (MCP-1), interleukin 18 (IL-18), macrophage inhibitory cytokine 1 (MIC-1), macrophage migration inhibitory factor (MIF), matrix metalloproteinase (MMP-9), and soluble forms of adhesion molecules were measured. Relatives had markedly lower insulin sensitivity (p=0.019) and higher serum MMP-9 (p<0.001) and MIF (p=0.006), but not other chemokines and biomarkers of endothelial function. Insulin sensitivity correlated negatively with serum MMP-9 (r=−0.23, p=0.045). Our data show that young healthy subjects with positive family history of type 2 diabetes already demonstrate an increase in some nonclassical cardiovascular risk factors.